Da’wah And Education; The Influence of Teachers' Debate Outcomes in Enhancing Student Motivation - Ismail Maidin; Sarip Adul; Saifulazry Mokhtar; Syamsul Azizul Marinsah (Fakulti Pengajian Islam, Universiti Malaysia Sabah, 2023)
This study is an in-depth review of the influence of the method of da’wah "mujadalah" or teacher-led debate on enhancing student motivation in an educational context. Debate is one of the methods of da’wah, and is also a teaching approach widely applied in education. However, the literature documenting the influence of the results of teacher-led debates on student motivation is still limited. The motivation behind this study was to address the prevalent confusion and misunderstandings surrounding the dual impact of debates, which can be both positive and negative. So, this literature review aims to explore existing research, related theories, and recent findings concerning the positive impact by relationship between the outcomes of teacher-led debates and the level of student motivation. This research employs a qualitative method; library analysis by gathering and analyzing relevant literature. The findings of this study that the outcomes of teacher-led debates among student, or teacher-student debate can enhance student motivation, and as dynamic platforms that actively stimulate the development and improving critical thinking, analytical skills and language skills among students if managed wisely. Among these is the situation where a teacher intentionally concedes or attempts to win the debate as one of the directed methods to motivate their students. The implications of this research are that teachers need to understand how the outcomes of their debates influence student motivation and how they can maximize this influence for the success of student learning and motivation.